Challenges in the Virtual Geometry Assurance of Proton Exchange Membrane Fuel Cell Stacks - Roth, Martin; Bickel, Sebastian; Götz, Stefan; Wartzack, Sandro (Procedia CIRP, 2024)
Hydrogen-powered fuel cells will play a vital role in the next generation of energy systems. In this regard, Proton Exchange Membrane Fuel Cells (PEMFC) represent a promising technical solution for all applications where direct electrification is not technically feasible or economically viable, such as the propulsion of heavy vehicles. However, robust production of high-quality fuel cell systems in scalable series production can only be achieved by an early assurance of the product quality considering the numerous variations on geometry element, part, and assembly level. This article presents the challenges and outlines the vision of a geometry assurance process capable of simulating the probabilistic assembly behavior of PEMFC stacks by multi-physics variation simulation, e.g., considering aspects of Finite Element Analysis and Computational Fluid Dynamics, under a realistic representation of the part manufacturing and assembly processes and their operation under variations. The findings reveal future research directions fostering the series production of robust, high-quality PEMFC stacks.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Geometry Assurance; Multi-physics Simulation; Proton Exchange Membrane Fuel Cell; Tolerancing